A Neuroscience Review of the Letter of Ali Imran 190-191 - Sena Sena (Universitas Muhammadiyah Enrekang, 2024)
Humans have advantages when compared to other creatures, namely being able to use their minds. Like other creatures, Allah has also given them minds. Mind which comes from the word 'aqala ya'qilu 'aqlan can be called neuroscience. In the review of philosophical science, humans are thinking animals (hayawanun natiq), where by Allah ASWT humans are given a special task as khalifah fil ardh to manage and prosper this earth. This task as a khalifah requires sufficient knowledge, must have a smart brain or really optimize their intellectual abilities as best they can and like to contemplate Allah's creations in this universe. As Allah says in the Qur'an Surah Ali Imran [3]: 190-191,